Adopsi Standar AAOIFI pada BMT di Wilayah Eks Karsidenan Banyumas : Tinjauan Karakteristik Inovasi - Hastin Tri Utami (el-Jizya: Jurnal Ekonomi Islam, 2021)
This study aims to determine the effect of relative advantage AAOIFI accounting standards, compatibility AAOIFI accounting standards, complexity AAOIFI accounting standards, trialability AAOIFI accounting standards and observability accounting standards AAOIFI partially to the adoption of AAOIFI accounting standards in the ex Karsidenan Banyumas. The population in this study is the accounting staff in the ex Karesidenan Banyumas. Sampling using purposive sampling method. The number of respondents in this study is 32 BMT accounting staff in the ex Karesidenan Banyumas. Hypothesis testing using multiple linear regression analysis method. The result of the test and analysis using multiple linear regression method shows that the relative advantage, compatability, complexity, trialability, and observability have a positive, significant effect towards the adoption of AAOIFI Accounting standard. Limitation of this study is (1) independent variables used in this study only pay attention to internal factors adopter that is characteristic of innovation just like relative advantage, compatability, complexity, ease to try and ease of observation.